The water festival in Puquio - Valiente, Teresa (1986)
Puquio, capital of the province of Lucanas, is located to the southwest of the department of Ayacucho, approximately 180 km. from Huamanga, capital of the department, and 480 km southeast of Lima. Puquio is at a height of 3,200 m.a.s.l. and extends from the central part of the hillside to the top of a hill surrounded by various fields of cultivation. In 1941, Puquio had 7,000 inhabitants, in 1961 there were 10,000 and in 1977 the population had increased to 16,000 inhabitants. The most important open in the region adjacent to the Puquio region is the Sillanayok: the Pedrorko plays the most important role in the Water Festival.